Mitochondrial dynamics in health and disease - Yapa, Nethmi M.B.; Lisnyak, Valerie; Reljic, Boris; Ryan, Michael T. (FEBS letters, 2021)
In animals, mitochondria are mainly organised into an interconnected tubular network extending across the cell along a cytoskeletal scaffold. Mitochondrial fission and fusion, as well as distribution along cytoskeletal tracks, are counterbalancing mechanisms acting in concert to maintain a mitochondrial network tuned to cellular function. Balanced mitochondrial dynamics permits quality control of the network including biogenesis and turnover, and distribution of mitochondrial DNA, and is linked to metabolic status. Cellular and organismal health relies on a delicate balance between fission and fusion, and large rearrangements in the mitochondrial network can be seen in response to cellular insults and disease. Indeed, dysfunction in the major components of the fission and fusion machineries including dynamin‐related protein 1 (DRP1), mitofusins 1 and 2 (MFN1, MFN2) and optic atrophy protein 1 (OPA1) and ensuing imbalance of mitochondrial dynamics can lead to neurodegenerative disease. Altered mitochondrial dynamics is also seen in more common diseases. In this review, the machinery involved in mitochondrial dynamics and their dysfunction in disease will be discussed.